Android Educational Game for Criminology Students - Guiamarudin S. Daud (RIRAI Publisher, 2022)
The researcher developed an app for Criminology students; the focus of this project is to provide them with a mobile educational game that could help them boost their mental awareness on topics and knowledge in the field of criminology. Target users are criminology students. Moreover, the user of this game will be addressed by the proponent to develop this system. Thus, it develops an android game application dedicated to criminology students. Promote criminology students’ knowledge and awareness in a more intuitive and enjoyable way and create and establish a 100% functional android-based application. The programming language used was JAVA, which is specialized in mobile game development. The integrated development environment (IDE) used was Eclipse JUNO, a standalone programming environment that is suitable for the coding structure and interface design of the developed system. A graphic editing tool was also utilized to further enhance the objects used in the game. The finished app was tested using the android tablet model Cloud pad 701 TV having Android 4.2.2 version firmware. The Codified Project Management Framework was then used in the development of the project. Based on the result of the Interface of the system obtained, the Android App concept for criminology students is effective and excellent. It was further recommended that the developed app still be reviewed thoroughly in terms of its data content validity. It was also recommended that the system will be developed further for more additional features.